'You don't have enough letters to make this noise': Arabic speakers' creative engagements with the Roman script. (January 2018) - Panović, Ivan
Abstract: Drawing on data collected primarily among young Egyptians, in this paper I discuss script-fusing – a literacy and semiotic practice of combining letters from two scripts, in this case Arabic and Roman, within a single word. I focus on its employment in digital environments, particularly Twitter, where some Arabic speakers adopt it to stylize their screen names. As a springboard for an analysis of the metalinguistic commentary on this practice, provided by several Twitter users and one Egyptian graphic designer, I offer a historicized interpretive framework for thinking through its creative potential and social semiotics by discussing it against the backdrop of Franco, an alternative way of writing Arabic using the Roman script supplemented by digits. Franco practices emerged as a response to technological constraints in the early days of the internet when Arabic script was not supported. This is no longer the case, but Franco has nevertheless not disappeared: not only is it still occasionally used for digital writing, it has also become a literacy resource used in a variety of offline domains. I argue that, instead of becoming redundant for writing Arabic, the Roman script is being further appropriated, resemiotized and aestheticized through acts of fusion with the Arabic script. Its cultural biography in Egypt (and arguably the Arab world) thus shows itself as a trajectory from a practically oriented, often contested, creative working around the technologically-induced lack of script choice, to an aesthetically, and at times ideologically, motivated engagement with the current profusion of linguistic and semiotic resources that are creatively blended together in acts of indexing and, indeed, iconicizing modern Egyptian and Arab cosmopolitanisms.